2021
DOI: 10.1007/s11926-021-00980-5
|View full text |Cite
|
Sign up to set email alerts
|

Blood Biomarkers for Monitoring and Prognosis of Large Vessel Vasculitides

Abstract: Purpose of Review Large vessel vasculitides (LVVs) are inflammatory conditions of the wall of large-sized arteries, mainly represented by giant cell arteritis (GCA) and Takayasu arteritis (TA). The inflammatory process within the vessel wall can lead to serious consequences such as development of aneurysms, strokes and blindness; therefore, early diagnosis and follow-up of LVV are fundamental. However, the arterial wall is poorly accessible and blood biomarkers are intended to help physicians n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 106 publications
1
27
0
1
Order By: Relevance
“…As novel biomarker candidates, proteins released by macrophages important in the pathology of GCA may provide a source of biomarkers for diagnosis and tracking disease activity. Indeed, levels of macrophage products such as soluble CD163, YKL-40, Angiopoietin-2 (Angpt-2), IL-33, VEGF, MMP-9, calprotectin and osteopontin were found elevated in the serum of GCA patients compared to healthy donors [51,[104][105][106][107][108][109][110][111][112] (Figure 3). Several markers are altered in GCA compared to healthy controls.…”
Section: A Serum Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…As novel biomarker candidates, proteins released by macrophages important in the pathology of GCA may provide a source of biomarkers for diagnosis and tracking disease activity. Indeed, levels of macrophage products such as soluble CD163, YKL-40, Angiopoietin-2 (Angpt-2), IL-33, VEGF, MMP-9, calprotectin and osteopontin were found elevated in the serum of GCA patients compared to healthy donors [51,[104][105][106][107][108][109][110][111][112] (Figure 3). Several markers are altered in GCA compared to healthy controls.…”
Section: A Serum Markersmentioning
confidence: 99%
“…Some studies reported markers to differentiate GCA patients from patients with isolated polymyalgia rheumatica (PMR). There is currently no macrophage markers to discriminate between GCA and infection (e.g., respiratory and urinary infection) [51,[104][105][106][107][108][109][110][111][112].…”
Section: A Serum Markersmentioning
confidence: 99%
“…Biomarkers can be used to diagnose or monitor disease activity for TA, which was given a minute description in related articles [87][88][89]. These biomarkers include tumor necrosis factor (TNF-α), vascular endothelial growth factor (VEGF), interleukins (ILs), pentraxin-3 (PTX-3), matrix metalloproteinases (MMPs), serum amyloid A (SAA), and chitinase-3-like protein 1 (YKL-40), and so on.…”
Section: Potential Biomarkersmentioning
confidence: 99%
“…In addition, there are other potential blood biomarkers for monitoring the progress of TAK [ 4 ], such as pentraxin-3 [ 5 ], YKL-40 [ 6 ], MMP-9 [ 7 ], MMP-3 [ 8 ], leptin [ 9 ], and serum amyloid A [ 9 ]. However, the diagnostic efficacies of these biomarkers have not been clinically validated.…”
Section: Introductionmentioning
confidence: 99%